Legislative drafting and the appropriate delineation of administrative power - Bednar-Giyose, Jeannine (My University, 2018)
This research explores and discusses how the discipline of legislative drafting can and should be applied in order to provide for the appropriate delineation of administrative power in legislation. This inquiry is situated at the intersection of administrative law and legislative drafting. The important role of legislation as a primary source of administrative law has been recognized in the literature. However, the application of the discipline of legislative drafting and its role in the development of administrative law has not yet been considered. This thesis provides an approach for how drafters can approach their discipline so that legislation is developed that it is consistent with, and to the extent necessary, is incorporated within, an integrated system of administrative law. The primary question that is explored in this research is how legislative drafting can be applied to achieve the objective of producing ‘effective’ or ‘quality’ legislation that delineates administrative power appropriately. To address this question, the research first examines the relationship that exists between legislative drafting and administrative law. Then a tailored theoretical framework is developed that can be applied by legislative drafters to guide and form the basis for an assessment of the delineation of administrative power in legislation, both during the development of legislation, and after the legislation’s enactment. Finally, this thesis explores how the tailored theoretical framework that has been constructed can be applied to the development and ongoing assessment of both principal and delegated legislation. In this regard, reference is made to a range of existing legislation, and specific proposals are provided for improving the drafting of types of legislative provisions that are important in relation to the control and delineation of administrative power.
A thesis submitted in accordance with the requirements for the degree PhD in Law
Keywords: Administrative law-South Africa; Law reform-South Africa